1973
DOI: 10.1111/j.1476-5381.1973.tb08358.x
|View full text |Cite
|
Sign up to set email alerts
|

The relation of adenyl cyclase to the activity of other ATP utilizing enzymes and phosphodiesterase in preparations of rat brain; mechanism of stimulation of cyclic AMP accumulation by adrenaline, ouabain and Mn++

Abstract: Summary1. The mechanism of stimulation of cyclic adenosine 3',5'-monophosphate (cyclic AMP) accumulation by adrenaline and ouabain and the effect of Mn++ substitution for Mg+ + as the metal ion requirement of this system was studied in cell-free preparations of adenyl cyclase from rat brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1975
1975
1977
1977

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Nevertheless, using other specific stimulatory agents such as glucagon (Mier & Urselmann, 1970) and isoproterenol (Duell et al, 1971) we found additional electron-dense deposits at the cell surfaces in the upper layers and, more distinctly, in the lower layers of normal epidermis. Since catecholamines stimulate adenyl cyclase activity without stimulation of other ATP utilizing enzymes (Katz & Tenenhouse, 1973), this cytochemical reaction was considered to be due to adenyl cyclase activity in these regions. Moreover, the inhibitory efl"ect of propranolol on the isoproterenol stimulation provided strong evidence supporting this suggestion.…”
Section: (I) Atp Hydrolasesmentioning
confidence: 99%
“…Nevertheless, using other specific stimulatory agents such as glucagon (Mier & Urselmann, 1970) and isoproterenol (Duell et al, 1971) we found additional electron-dense deposits at the cell surfaces in the upper layers and, more distinctly, in the lower layers of normal epidermis. Since catecholamines stimulate adenyl cyclase activity without stimulation of other ATP utilizing enzymes (Katz & Tenenhouse, 1973), this cytochemical reaction was considered to be due to adenyl cyclase activity in these regions. Moreover, the inhibitory efl"ect of propranolol on the isoproterenol stimulation provided strong evidence supporting this suggestion.…”
Section: (I) Atp Hydrolasesmentioning
confidence: 99%